Regional Consumption And Income Dynamics In Turkey: A Panel Data Analysis - Güven, Murat (Institute of Social Sciences, 2018)
Examining regional consumption and income dynamics has become increasingly important in recent years. Regional income and consumption disparities are used to create regional economic policies because the reduction of these disparities is a crucial step for economic development. The rapid progress of the scientific and technological developments in communication technologies and the promotion of the air, land and marine transportation in recent years have increased the interactions among households at the regional level. Thus, the differences in consumption and income among households have been changing. This thesis thus aims to test whether there are any differences in consumption and income among the 26 NUTS-2 regions in Turkey, then to identify the determinants of the differences and finally to examine the direction in which these differences evolve over time. For this purpose, demand elasticities are estimated at the regional level for each group of goods and service, then regional convergence analyzes is tested. The price and income elasticities for 12 groups of goods and service for 26 NUTS-2 level regions covering the period 2005-2013 are estimated using the Almost Ideal Demand Model(Deaton & Muellbauer, 1980) in the linear form.

Bölgesel düzeyde tüketim ve gelir dinamiklerinin incelenmesi ülkemizde son yıllarda önemli hale gelmektir. Bölgesel gelir ve tüketim farklılıkları bölgesel ekonomik politikaların olusturulmasında kullanılmaktadır, çünkü bölgesel gelir ve tüketim farklılıklarının azaltılması ekonomik kalkınma açısından çok önemli bir aşamadır. Son yıllarda iletişim teknolojilerindeki bilimsel ve teknolojik gelişmeler ve hava, kara ve deniz ulaşımının teşvik edilmesi, bölgesel düzeyde hanehalkları arasındaki etkileşimi artırmaktadır. Böylece, hanehalkları arasında tüketim ve gelir farklılıları değişmektedir. Bu tez Türkiye'deki 26 İBBS Düzey-2 bölgesi arası tüketim ve gelir farklılılarının olup olmadığını test etmeyi, daha sonra bu farklılıklarının belirleyicilerini tespit etmeyi ve son olarak da bu farklılıkların zamanla nasıl bir değişim gösterdiğini bulmayı amaçlamaktadır. Bu amaçla bölgesel düzeyde her bir mal ve hizmet grubu için esneklikler hesaplanmış, daha sonra bölgesel yakınsama analizleri yapılmıştır. 26 İBBS Düzey-2 bölgesi için 2005-2013 yılları arasında 12 mal ve hizmet grubu için fiyat ve gelir esneklikleri lineer formda mükemmele yakın talep modeli(Deaton & Muellbauer, 1980) kullanılarak hesaplanmıştır. Gıda, alkollü içecek, giyim, konut, mobilya, sağlık, ulaşım, haberleşme, eğlence, eğitim, lokanta ve diğer mal ve hizmet harcamaları için esneklikler coğrafik olarak ağırlıklandırılmış panel regresyon(Bruna & Yu, 2013;Yu, 2010) tekniği kullanılarak elde edilmiştir.
Türkiyede Bölgesel Tüketim Ve Gelir Dinamikleri: Panel Veri Analizi
Thesis (M.A) -- İstanbul Technical University, Institute of Social Sciences, 2018
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Economics; Ekonomi